Brain Damage Treated with Non Proven Intensive Training 2003-2011: A Norwegian Cost Analysis - Norum, Jan; Tjeldnes, Knut; Ramsvik, Arnborg (Global Journal of Health Science, 2012)
There has been an increased request for intensive training and rehabilitation of patients with brain damage in Norway. These programs are demanding with regard to personnel, travelling, time and economic resources. We aimed to indicate cost and gain to make these programs cost-effective. A retrospective study included all patients referred to the Northern Norway Regional Health Authority (NNRHA) trust during the nine years period 2003-2011. All referrals to the NNRHA trust for the economic coverage of foreign based rehabilitation or habilitation programs (The Advanced Bio-Mechanical Rehabilitation (ABR), Institutes of Achievement of Human Potential program (IAHP) (Doman method), Family Hope Center (FHC) program and the Kozijavkin method) were included. 17 patients were detected and 15 fulfilled the inclusion criteria for funding. Median age was 8 years (1-31 years). Cost from the specialist health care point of view was calculated. A cut-off limit of €57,000/quality adjusted life year (QALY) and a 4% discount rate was employed. The undiscounted cost per patient enrolled was calculated €133,210 (discounted €121,348). To make these therapies cost effective, a total of at least 2.13 QALYs (2.34 undiscounted QALYs) must be gained per patient enrolled. Such a gain could not be indicated and we doubt it is achievable. Non-proven intensive training programs for patients with brain damage are costly. As long as their effect has not been documented, health care services should not spend resources on these programs outside clinical trials.